Penggunaan sutur dalam bidang perubatan: Analisis dari perspektif Sains dan Islam / Nur Farhani Zarmani - Nur Farhani, Zarmani (2017)
Halal certification practices are growing due to the rapid development of the global halal industry. It is no longer confined to food products, but has now encompassed a wide range of products such as consumables, cosmetics, toiletries, and pharmaceutical products. There is a recent demand for halal certification from another healthcare sector which is medical devices, which covers all types of medical equipment used in hospitals from simple equipment such as bandages to complex equipment such as ventilators. This matter has been raised by the industry as halal labeling is not only an added value to products, but is also a requirement to penetrate the market of Islamic countries such as Saudi Arabia, Turkey and Pakistan. Nevertheless, the halal certification for medical device products has yet to be implemented due to non-availability of standards or guidelines that can be applied to produce halal medical devices. In reality, not all medical devices need to be labeled as halal, instead only devices that incorporate animal tissues, in contact with or invasive to the body, and produce reaction to body. Therefore, this study will focus on the halal issues related to medical devices through a study on a device that not only meets all four criteria, but is also one of the devices that are widely used to stitch and close the wounds of patients after surgery or injury, namely sutures. In addition, this study also analyzes the content of selected sutures in the local market from the perspective of science, besides clarifying the legal use of sutures from the perspective of Islamic ruling. To achieve these objectives, qualitative research method involving data collection through library research, as well as field studies involving laboratory testing and in-depth interviews with industry players, the authorities of the medical device, the authorities of religion and experts on Islamic ruling and practitioners. The data collected were then analyzed using inductive, deductive, comparatives and content analyses. The results show that halal issues in the supply chain of sutures exist in the selection of raw materials, followed by the manufacturing, distribution and the use of sutures in hospitals. In addition, the laboratory analysis shows that there was no prohibited source such as porcine elements in the content of sutures, but there exists elements of vertebrates. With regard to the status of resources, processes, reactions and the effects on the use of sutures in the medical field, this study found that there is a diversity of Islamic ruling, and there is room for the application of methods such as al-istihlak, al-darurah and al-hajah. Therefore, the study also recommends a number of components in the development of halal medical device guidelines that combine aspects of halal and safety.